Digital manufacturing technology for sustainable anthropometric apparel. - Zakaria, Norsaadah (Woodhead Publishing, 2022)
Digital Manufacturing Technology for Sustainable Anthropometric Apparel is a thorough and practical examination of the state-of-the-art in anthropometric apparel manufacturing technology. The scale of the textiles industry, in economic as well as environmental terms, is so significant that new technologies and techniques that deliver improvements are of great global interest. Consumer preferences and government regulations are causing apparel manufacturers to prioritize sustainable practices, and at a time of unprecedented technological evolution and competitive pressure, integrating these measures with other priorities is a key challenge. By combining the expertise of contributors from the worlds of technology change management and technical textiles engineering, this book provides a unique interdisciplinary resource for organizational as well as technical implementation. Newly developed Industry 4.0 technologies are addressed, along with the latest data collection and analysis methods.